MOLUSKA DI PESISIR BARAT PERAIRAN SELAT LEMBEH, KOTA BITUNG, SULAWESI UTARA - Arbi, Ucu Yanu (Bumi Lestari Journal of Environment; Vol 10 No 1 (2010), 2010)
Observation on molluscs on western coastal zone of Lembeh Strait waters, Bitung City was conducted on April 2008 and March 2009. Western coastal zone of Lembeh Strait waters has environmental degradation. Molluscs as one of occupier marine live in this area. The observation was aimed to find out an idea on the condition of molluscs at western coastal zone of Lembeh Strait waters. It was made at 5 stations. Molluscs samples in quadrant transect line were counted and identify. Trachycardium flavum (Cardiidae) class of Pelecypoda were the common and widely distributed molluscs. Molluscs community on western coastal zone of Lembeh Strait waters on medium diversity. The highest diversity index (H) (1.149) was found at Station 4 and the lowest (1.180) was found at Station 3. An evenness index (J) was 0.842 to 0.973 and richness index (D) was 43.62 to 68.82.